Divergent geographic patterns of genetic diversity among wild bees: Conservation implications. Issue 12 (24th July 2018) - Lecocq, Thomas; Michez, Denis; Gérard, Maxence; Vereecken, Nicolas J.; Delangre, Jessica; Rasmont, Pierre; Vray, Sarah; Dufrêne, Marc; Mardulyn, Patrick; Dellicour, Simon
Abstract: Aim: Genetic diversity is a key factor to species survival. This diversity is unevenly distributed across the species range, delimiting genetic diversity hotspots (GDH). Focusing conservation efforts on regions where GDH of several species overlap (i.e., multispecies GDH) could rationalize conservation efforts by protecting several taxa in one go. However, recent studies suggest the existence of many species‐specific GDH. This would make spatially prioritizing protection even more challenging as it requires the integration of these multiple GDH rather than few hotspots into conservation planning. Here, we characterize GDH of nine co‐distributed bee species through an original comparative mapping approach to assess the suitability of a spatial prioritization strategy to protect their genetic diversity. Location: We studied bee populations from Europe. Methods: First, we used a sliding window approach to estimate the nucleotide diversity and its geographic distribution to highlight GDH of each species. Second, we assessed the overlap of GDH between species by generating consensus maps based on the species‐specific maps of nucleotide diversity. Third, we used the GDH distribution patterns to identify the extent of cost‐effective area network that would be needed to protect genetic diversity of all nine species. Results: Genetic diversity was unevenly distributed across species ranges, but we found no evidence of a large overlap among GDH from all species. Cost‐effective area network needed to protect genetic diversity of all species spreads over several large geographic areas including regions under high human development pressures. Main conclusions: Genetic diversity hotspots' location is species‐specific. Therefore, focusing conservation efforts strictly on the few regions harbouring GDH for many bee species is unlikely to be sufficient to ensure long‐term persistence of all species. Conservation actions should be implemented simultaneously in different regions according to a complementary‐based conservation approach, to optimize the conservation of all bee diversity.